Hydrodynamic Performance of Half Pipe Breakwaters Experimentally and Numerically - Badr Hussein, Karim; Ibrahim, Mohamed; Awaad, Ahmed Sh.; Abd El Ghany, Samah H. (Transactions on Maritime Science, 2024)
The main objective of constructing barriers is to safeguard harbours and shores from waves and sea currents. This paper aims at presenting a study on innovative and non-traditional alternatives to breakwaters, experimentally and numerically, to assess the hydrodynamic efficiency of the suggested models in order to choose the most appropriate one. Two models of semi-submersible-type breakwaters have been studied, in the form of a cross-section of a half pipe with an internal diameter and thickness of 30.00 and 1.00 cm, respectively. Model (a) is a circular half-pipe with an upward concave, whereas model (b) has a sideways concave towards the water. Several scenarios for the breakwaters suggested in this study have been simulated using FLOW 3D. The results indicate that the transmission coefficient (Tc), provided by model (b), is 3-7% lower than model (a), while the reflection coefficient (Rc) values for model (b) are 4-8% higher than model (a). The results show that model (b) has a 10% lower (Tc) at d/h = 0.80 compared to d/h = 0.60, while (Rc) is 8% higher at d/h = 0.80 than at d/h = 0.60 for the same model. The suggested breakwater reduces inclined waves' energy more quickly than perpendicular waves. Regarding the hydrodynamic performance, the proposed breakwater in model (b) is shown to be more efficient and effective than the breakwater in model (a), so it is recommended to use it due to its effectiveness in providing protection for coastal wave zones and benefiting from the energy of waves to generate electricity.